Vpliv bolezni in škodljivcev na obnovo gozdov - Ogris, Nikica (Gozdarski vestnik, 2017)
Tree diseases and pests have huge impact on the forest ecosystem health at all development stages. In this paper we mention some of the most common and important diseases and pests in terms of renewal, rejuvenation of forests. We emphasize that it is necessary to: (1) improve the whole chain from seed to viable plants in the woods; (2) In addition to providing healthy seedlings assure a system that will provide quality seedlings, a standard or quality manual, which will define the required morphological characteristics of quality seedlings, the method of excavation, transport, manipulation of seedlings before planting, methods of planting and care after planting, on which the success of artificial reforestation with planting depends; (3) Provide regular tests for the presence of hidden, latent, and cryptic pests, with emphasis on the genus Phytophthora in forest nurseries.
Keywords: forest disease; varstvo gozdov; pest; bolezni gozdov; drevesni škodljivci; forest seedling; young forest; drevesne sadike; drevesno mladje; forest seed; forest regeneration; seme; forest rejuvenation; pomlajevanje; obnova gozdov; forest nursery; drevesnice